520 Long term follow up after diagnosis of gestational trophoblastic disease. (4th December 2020) - Freitas, Pedro Corvelo; Mira, Beatriz; Guimarães, António; Opinião, Ana; Nunes, Hugo; Jorge, Ana Francisca; Vaz, Fátima; Moreira, António
Abstract : Introduction/Background: The spectrum of Gestational trophoblastic disease (GTD) ranges from pre-malignant conditions of complete (CHM) and partial (PHM) hydatidiform moles to the malignant invasive mole, choriocarcinoma (CC) and very rare placental site trophoblastic tumour/epithelioid trophoblastic tumour (PSTT/ETT). Gestational trophoblastic neoplasia (GTN) are highly responsive to chemotherapy (CT) and with appropriate diagnosis and management a high cure rate (>90%) is observed. In this study we reviewed the outcomes of long term follow up for GTN patients (pts) treated in our centre. Methodology: Update of outcomes (clinical records and phone contacts) of patients with GTN tumours treated in our centre between January 2005-December 2014. Results: Twenty three GTD pts between 2005–2014: 2 PHM (9%) and 9 CHM (39%), 8 CC (35%), 2 ETT (9%) and 2 PSTT (9%). Median age at diagnosis: 37 years (20–53). Staging: 12 stage I (52%), 9 stage III (39%) and 2 stage IV (9%). Most patients received CT as first treatment (20; 87%), according to prognostic risk score: 10 with methotrexate (MTX) monotherapy (50%) and 10 with EMA-CO (50%). Resistance to first line CT was observed in 5 patients (22%), 2 after MTX monotherapy and 3 after EMA-CO. For those pts, 2nd line CT was as follows: 1- ACT-D; 1 -EMA-CO (after MTX monotherapy) and 3-EMA-EP (after EMA-CO). Surgery was performed in 9 pts: 6 because of residual disease after CT and in 3 cases as the only treatment (1 patient with ETT and 2 patients with PSTT). One patient without criteria for treatment underwent clinical surveillance. Treatment related adverse reactions- Significant CT toxicity was observed in 2 pts (1-pneumonitis, 1- sarcoidosis), both with clinical resolution after specific care. One pt complained of late surgical sequelae (adhesions) and still hasn´t recovered. After a median follow up of 69 months, 2 patients died: 1 due to a second malignancy (glioblastoma), 1- due to acute respiratory failure (extensive lung metastasis in previous chronic lung disease). Five patients maintain FU at our centre and 17 were either referred to their primary care physician (9) or were lost to follow up (7). Second neoplasia was observed in 3 pts:1-glioblastoma, 1- thyroid papillary carcinoma, and 1- gallbladder polyps. Conclusion: GTD is a rare diagnosis and duration of follow is controversial. Our data suggests that prompt management of serious CT adverse reactions is important to prevent the late term impact of CT toxicities. Second neoplasia in survivors of GTD deserve further study. Disclosures: No disclosures to report.